2006
DOI: 10.1111/j.1365-246x.2006.02878.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aftershocks in a lithospheric model with seismogenic zone governed by damage rheology

Abstract: S U M M A R YWe perform analytical and numerical studies of aftershock sequences following abrupt steps of strain in a rheologically layered model of the lithosphere. The model consists of a weak sedimentary layer, over a seismogenic zone governed by a viscoelastic damage rheology, underlain by a viscoelastic upper mantle. The damage rheology accounts for fundamental irreversible aspects of brittle rock deformation and is constrained by laboratory data of fracture and friction experiments. A 1-D version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
187
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(206 citation statements)
references
References 57 publications
19
187
0
Order By: Relevance
“…Yet this period marks the transition from mainshock to aftershocks, and holds valuable information about the underlying mechanisms that control the aftershock occurrence [e.g., Nur and Booker, 1972;Das and Scholz, 1981;Dieterich, 1994;Ben-Zion and Lyakhovsky, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Yet this period marks the transition from mainshock to aftershocks, and holds valuable information about the underlying mechanisms that control the aftershock occurrence [e.g., Nur and Booker, 1972;Das and Scholz, 1981;Dieterich, 1994;Ben-Zion and Lyakhovsky, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The compliance, or inverse of viscosity (C v Áda/dt), relates the deviatoric stress to the rate of irreversible strain accumulation. BEN-ZION and LYAKHOVSKY (2006) connected the rate of irreversible strain accumulation with partitioning between seismic and aseismic deformation in the seismogenic zone, and showed that the fraction of elastic strain released seismically, referred to as the seismic coupling coefficient v, can be estimated as:…”
Section: Discussionmentioning
confidence: 99%
“…LYAKHOVSKY et al (2001) and BEN-ZION and LYAKHOVSKY (2006) suggested that damage zone structure is primarily controlled by (1) the ratio between loading rate and healing rate, (2) the overall degree of ''brittleness'' of crustal deformation which may be parameterized by the seismic coupling coefficient v, and (3) the susceptibility to propagation of rupture associated with dynamic weakening and related dynamic time scale s r . Below we review the main material parameters and outline their effect on fault zone evolution.…”
Section: Damage Model Parametersmentioning
confidence: 99%
“…This damage rheology is applicable to volumes with a sufficiently large number of cracks that allow quantitative description through properties of the crack distribution rather than those of the individual cracks MYASNIKOV, 1984, 1985). Detailed reviews and recent developments of the model can be found in LYAKHOVSKY (2006) and, examples of model applications showing the dominant role damage processes play in the evolution of fault systems and their internal structure can be found in FINZI et al (2009. Here we only summarize the main ingredients of the model that are relevant for our work.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The damage-related viscosity enables representation of the permanent inelastic deformation before brittle failure associated with micro-crack growth and frictional sliding between grains (HAMIEL et al, 2004a, b). Various studies have shown it is required to adequately describe processes such as subcritical crack growth and aseismic deformation in the seismogenic crust BEN-ZION and LYAKHOVSKY, 2006). Combining Eqs.…”
Section: Time Integration Scheme For the Damage Rheologymentioning
confidence: 99%